“I Don't Know How to Work upon My Skin from Within” (A Bodily Aspect of Self-Narration) - Lavrinec, Jekaterina (Problemos, 2008)
In the article a typology of bodily self-experience is discussed, concentrating on three existential situations: 1) body as an exposed surface (bodily practices of dandyism); 2) body as a surface which cannot be consciously controlled (a common experience of being photographed, described by Roland Barthes); 3) bodily knowledge which is discovered after a loss of memory (autobiographic experience of old Lev Tolstoy). It is claimed that photography and writing are “media of self-awareness”, provoking thematization of bodily experience and problematization of the concepts of “representation” and “identity” – which are examined on the material of three types of bodily experience: 1) consciously constructed body (body as a tool for charming); 2) uncontrolled body (body as a trouble spot); 3) body an experience of “here and now”.